Sistem Informasi Pemasaran Perseroan Terbatas ( PT) Bintang Fajar Sukoharjo - Mulyadi - Universitas Surakarta; Joko Wandyatmono - Universitas Surakarta (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2017)
ABSTRACT: Companies today have to think about the business and mission critical corporate marketingstrategy. Companies generally move in the market and competition are already known, and certainly, orthe choice of stable customers, but the war in a constantly changing business competition, technologicaladvances, trade policies are managed and fall of the loyalty of the customers. Companies competing inthe race and the rules and guidelines that must be changed, the line does not end and no